Flood Vulnerability Mapping Using Geographic Information System (GIS) in Gajah Wong Sub Watershed, Yogyakarta County Province - A. Ardiansyah; Dyah Respati Suryo Sumunar (Department of Geography Education, University of Jember, 2020)
Gajah Wong Sub Watersheds frequently hit by floods which are potentially damaging. Therefore, a study on a flood vulnerability of the area is deemed necessary. This study aims to map floods vulnerability, to know the level and its spread in Gajah Wong Sub Watershed of Yogyakarta County Province by using Geographic Information System (GIS). The methods implemented in this study was weighting and scoring analysis and overlay of parameter attributes data of flood vulnerability framer, consisting of land use, slope of mountain, rainfall, soil type, geology, height of location and river buffer. Each parameter of flood vulnerability framer is classified based on the magnitude of effect towards flood vulnerability. The results of this study indicate that there were three levels of flood vulnerability in Gajah Wong Sub Watershed, i.e. low flood vulnerability of 338.34 Ha (6.86%), medium flood vulnerability level of 4,595.62 Ha (93.13%) and high flood vulnerability level of 0.76 Ha (0.02%). Low flood vulnerability level is ditributed randomly to all areas of Gajah Wong Sub Watershed cover of Ngaglik Sub-district, Depok Sub-district, small part of Pleret Sub-district and was predominantly in Banguntapan Sub-district, an area with rainfall. Medium flood vulnerability areas dominated Gajah Wong Watershed. Meanwhile, high flood vulnerability level occupied small portion of the area and spread in the southern part of Pleret Sub-district which was taken as the area of River Buffer analysis. Keywords: GIS; Gajah Wong; Sub Watershed; Yogyakarta. Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License